Investigation on the effect of machining pazrameters on 42CrMo4 DPS steels. Issue 1 (31st December 2023) - Y M, Shivaprakash; BM, Gurumurthy; Hindi, Jamaluddin; K, Muralishwara; Sharma, Sathyashankara
Abstract: Machining 42CrMo4 martensite—ferrite dual phase steel is challenging due to its high hardness and it is essential to determine the favorable requirements for the optimum machining condition. The ability to alter the martensite quantity in dual phase structure of steel leading to variation in bulk hardness is the motivation for machinability investigation. In heavy duty machining, the determination of tool life and surface roughness at various conditions of machining plays an important role in the manufacturing industry. In the present work, machinability tests are carried out on 42CrMo4 martensite—ferrite dual phase steel to assess the tool life and surface roughness. Speed, feed, and depth of cut are varied in different levels. The tests are carried out as per the full factorial method. A microstructure study is performed to correlate the various mechanical properties with phase morphology. The main objective of this study is to obtain the optimized machining process parameters for the turning operation of 42CrMo4 martensite—ferrite dual phase steel. All cutting tests are carried out under dry conditions using a carbide insert. Microstructure and mechanical property analysis shows an increase in the martensite quantity with the increase in the dual phase processing temperature. From the ANOVA results, it is found that the depth of cut is the major contributing factor to the variation of tool life and surface roughness within the range of values considered for the study. Microstructure analysis revealed the distribution of ferrite and martensite phases evenly. The optimum combination of machining parameters is calculated for obtaining a superior combination of tool life and surface roughness. The 42CrMo4 DPS steel may be used for structural applications with wide variation in the property range.